PEMBUATAN BIOBRIKET ARANG BERBASIS TANDAN KOSOSNG KELAPA SAWIT DAN ECENG GONDOK SEBAGAI SUMBER ENERGI ALTERNATIF YANG RAMAH LINGKUNGAN - Giyanto STP, MT (Institut Teknologi Sawit Indonesia (ITSI), 2019)
Growth population were very fast and caused demand to the energy increasingly while fuel ingredients fossilthinning out. The needed of energy alternative sources as energy biomass among them briquettes charcoal. Inanother, there are some potential biomass sources, one of that is empty bunch of oil pam. Briquettes charcoalfrom oil palm empty bunch could be an alternative to resolve limitations source power energy and at once asalternative. The material which used in this study were oil palm empty bunch and hyacinth mumps. Adhesivesare used is tapioca. The method used is press hydraulic with pressure Felts 0, 8 tons levels 10% adhesive.Charcoal processing used a modified drum. Charcoal obtained then pounded and then made ingredients traybriquettes charcoal. Briquettes charcoal made from 5 variations composition ingredients oil palm empty bunchand water hyacinth were 100%, 75 %: 25%, 50%: 50%, 25%: 75% with adhesive concentration 10% with adiameter of 2.15cm and 5.5 cm. The results of this study that best briquettes is TEG-1 treatment (100% bunchesblank with 10% adhesive produces) with value heat 5896 cal / g, water content 2.81%, content ash 20 %.